O Curso Normal do Centro de Ensino Graça Aranha nas representações memorais das normalistas egressas (1985 a 2004) - Silva, Roza Maria Soares da (Universidade do Vale do Rio dos Sinos, 2021)
In this research, we analyze the memorial representations that the teaching students, graduates of the Normal Course at the Graça Aranha High School Teaching Center, have about the school and its role in the city of Imperatriz and in the region of Tocantina. The end of the 20th century and the beginning of the 21st century are used as a time frame. Thus, it is considered to be based on the history of the present time, which brings to discussion the nuances of the Normal Course. A course that in its development under its own specificity, according to the needs arising from a municipality in Maranhão in full economic growth. The present investigation is anchored in the memorial representations of the graduates, which reveal important elements that meet authors who recognize that every public school institution, in its composition, maintains an organization and structure in accordance with the National Guidelines and Bases Law , in force, but which also maintains a link with the broader society in which it operates. In this movement, it is considered that the interactions and cultural exchanges that took place in the Graça Aranha Normal Course, translated into theory and practice, were the basis of pedagogical training so that the graduates became education professionals and became subjects in the fabric. between school and society. Written and oral sources contributed to emerge the story not only of the Normal Course, but also of social issues which pointed to the confirmation of the thesis that the course in question, offered by the Graça Aranha Teaching Center, had a important role in the development of the Political Educational Project of the Tocantins Region, specifically with regard to the training of primary teachers.
Keywords: Curso normal; Memórias e representações; Formação pedagógica; Normal course; Memories and representations; Pedagogical training; ACCNPQ::Ciências Humanas::História